THE INCREASE IN PUPILS WITH SLD AND SEN: POSSIBLE CAUSES AND INTERVENTIONS THROUGH LITERATURE REVIEW AND FIELD INVESTIGATION (Revista Educação Especial em Debate, 2024)
In recent years, there has been a significant increase in the number of children and young people with SLD (Specific Learning Disorders) and SEN (Special Educational Needs) present at school. Only recently has it been realized, thanks to research in the field, identified through a comprehensive literature review, that they are individuals with unique traits and specific learning modalities, to whom a specific operational response must be given. On the basis of the evidence that emerged in the literature, the University of Sassari carried out a qualitative-quantitative survey, as part of the Research Project of National Interest (PRIN), involving a sample of 1,034 teachers and educators from secondary schools of the first and second degree. Starting from the insights that emerged with the analysis of the literature, the present research was carried out, aimed at understanding: the possible causes of the increase in the presence of students with SLD and SEN, the most effective actions to involve families for the assessment and possible diagnosis, the most functional teaching activities for inclusion and the use of the most popular compensatory tools.